Evaluation of Monocarboxylate Transporter 4 (MCT4) Expression and Its Prognostic Significance in Circulating Tumor Cells From Patients With Early Stage Non-Small-Cell Lung Cancer - Markou, Athina; Tzanikou, E.; Kallergi, G.; Pantazaka, E.; Georgoulias, V.; Kotsakis, A.; Lianidou, E. (Frontiers in Cell and Developmental Biology, 2021)
Purpose: Monocarboxylate transporter 4 (MCT4) can manipulate the concentration of lactate in the tumor microenvironment and further regulate cancer cell proliferation, migration, and angiogenesis. We investigated for the first time the expression of MCT4 in circulating tumor cells (CTCs) derived from early stage Non-Small Cell Lung Cancer patients (NSCLC) and whether this is associated with clinical outcome. Experimental Design: Α highly sensitive RT-qPCR assay for quantification of MCT4 transcripts was developed and validated and applied to study MCT4 expression in CTC isolated through the Parsortix size-dependent microfluidic device from 53 and 9 peripheral blood (PB) samples of NSCLC patients at baseline (pre-surgery) and at relapse, respectively as well as we evaluated the ‘background noise’ by analyzing peripheral blood samples from 10 healthy donors (HD) in exactly the same way as patients. Results: MCT4 was differentially expressed between HD and NSCLC patients. Overexpression of MCT4 was detected in 14/53 (26.4%) and 3/9 (33.3%) patients at baseline and at progression disease (PD), respectively. The expression levels of MCT4 was found to increase in CTCs at the time of relapse. Kaplan-Meier analysis showed that the overexpression of MCT4 was significantly (P=0.045) associated with progression-free survival (median: 12.5 months, range 5-31 months). Conclusions: MCT4 overexpression was observed at a high frequency in CTCs from early NSCLC patients supporting its role in metastatic process. MCT4 investigated as clinically relevant tumor biomarker characterizing tumor aggressiveness and its potential value as target for cancer therapy. We strongly believe that MCT4 overexpression in CTCs merits to be further evaluated as a non-invasive circulating tumor biomarker in a large and well-defined cohort of patients with NSCLC.